The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jcot.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of distal end clavicle: A review

Abstract: Distal end clavicleNeer type 2 a b s t r a c t Management of fracture distal end clavicle has always puzzled the orthopaedic surgeons. Now-a-days with a relatively active lifestyle, patients want better results both cosmetically and functionally. Despite so much literature available for the management of this common fracture, there is no consensus regarding the gold standard treatment for this fracture. In this article, we reviewed the literature on various techniques of management for this fracture, both cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
86
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 54 publications
0
86
0
5
Order By: Relevance
“…However, there is no current gold standard for the treatment of these fractures. 3,12 Although nonsurgical treatment of Neer type II distal clavicle fractures has shown satisfactory outcomes for pain, function, and postinjury strength, there is a corresponding increase in the incidence of symptomatic nonunion, cosmetic deformity, and the need for delayed surgery. 13,14 A significant consideration with Neer type II fractures is the higher rate of nonunion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is no current gold standard for the treatment of these fractures. 3,12 Although nonsurgical treatment of Neer type II distal clavicle fractures has shown satisfactory outcomes for pain, function, and postinjury strength, there is a corresponding increase in the incidence of symptomatic nonunion, cosmetic deformity, and the need for delayed surgery. 13,14 A significant consideration with Neer type II fractures is the higher rate of nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…4 Larger epidemiologic studies have shown that 69% to 85% of clavicle fractures involve the middle one-third of the clavicle, and distal clavicle fractures may occur in 10% to 28% of cases. 3,[5][6][7] Operative management of midshaft clavicle fractures leads to significant functional limitations in up to 25% of military patients 1 year postopera-abstract…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although this type of fracture (and the operative possibilities) is already described by Neer in 1963, till this date there is no universally agreed standard operative procedure for displaced distal clavicle fractures. 5 We found two reviews and a meta-analyses concerning the treatment of a distal clavicle fracture. Oh et al, found no statistical differences in union/non-union rates but more complications in the group treated with a hook plate or Kirschner wires in combination with Tension Band Wiring (TBW).…”
Section: Relevant Literature/discussionmentioning
confidence: 99%
“…The site of fracture also depends upon the age of the patient and mechanism of injury. 6 Elderly men-proximal third clavicle fracture Children-middle third clavicle fracture, undisplaced. Adolescents -middle third clavicle fracture, displaced Middle aged patient-distal third clavicle fractures.…”
Section: Incidence Of Injurymentioning
confidence: 99%